RESULTS OF 50-YEAR TESTING OF PROGENIES OF ENGLISH OAK PLUS-TREES AND BEST TREES - Los, S. A. (Forestry and Forest Melioration, 2018)
Introduction The main problem that hinders the further development of forest tree improving is the lack of long-term test data on plus trees and stands tested by growth and development of their progenies. Modern molecular genetics methods solve many important issues of forest tree improving, but do not allow predicting the expected growth rate and stemming straightness of plus trees progenies. For this reason, creation and investigations of progeny trials are the part of forest tree improving programs of many countries. In this regard, the progeny trial studies continue to be relevant, especially over the age of 20–30 years. The results of progeny testing give a possibility to analyze the objective laws of characteristic inheritance of forest woody plants and to identify the features of growth and development dynamics at the individual and family levels. The aim of the work is to summarize the results of the plus and best English oak trees progeny testing in the 50-year old trials in Kharkiv region. Materials and methods The studies were carried out in the oldest progeny trial of English oak in Ukraine created in 1958 in 98 quarter of Pivdenne Forestry of Kharkiv Forest Research Station of URIFFM. Plot area of 3 hectares is characterized by fertile and loamy soil. The acorns from the 313 open-pollinated progenies of plus and best normal English oak trees selected in 12 forest enterprises in the Kharkiv, Sumy, Donetsk, Mykolayiv, Poltava and Vinnitsa regions were sown during the object creation. The acorns from local provenance bulked sample were sown every 2–3 rows as a control. The investigation was carried out in 2008–2009 when the biological age of plants was 50 years old. Age of selected trees ranged from 44 to 300 years. For each tree, the survival, DBH, height, and selection category were recorded. The condition of the trees was determined by a modified scales based on oak viability categories and sanitary condition. The data were processed by variation statistics methods with the estimation of the significance of differences between the variants (offspring of certain trees) and the control. The variants indicators were compared to the data from growth course tables. To assess the selection quality of offspring in progeny trials the scale based on the distribution of trees by plant breeding categories within the variant was used. Results and Conclusions The progenies of the plus and best oak trees from Sumy (Left-bank Steppe), Mykolayiv and Donetsk (Step) have the best survival ability in Left-bank Forest-Steppe conditions in 50 years; the progenies from the Rivne (Polissya) and Vinnitsa regions (Right-bank Forest-Steppe) have the worst one. Among the 53 examined progenies, 27 (51 %) are the fastest growing ones. 7 progenies (Slovyansk-9, 11, Trostyanets-2, 11, 15, 16, 18) are noted for the best growth and quality. 4 progenies significantly rise over the control by height but have a satisfactory stem quality. 11 progenies are characterized by high stem quality and control-level height and diameter. Two progenies (Zhovtnevyy-26 and Trostyanets-2) exceed the control by more than 10 % in height and more than 30 % in diameter, so the parent (plus) trees of these progenies match the elite tree selection criteria. These trees can be recommended for creating the clonal seed orchard of the second level. 23 of 53 progenies exceed, on average, the control by stem volume of the average tree by 28.8 %. Slovyansk-1, -11, Volchansk-10, Zhovtnevyy-26, and Trostyanets-2 were the best on them. It should be noted that the control had a relatively high growth rate. Among the progenies of the best trees, which have not been included in the State Register of plus trees, 42.9 % are the fast-growing, but their stem quality is satisfactory. Among the progenies of plus trees, included in the current State Register, 70 % are fast-growing, and 45 % are of high stem quality. The moderate positive correlation between a branchless part of the stem of maternal trees and a share of trees of I and II selection categories of progenies has been detected (r = 0.33) suggesting the usefulness of branchless part of a stem in selecting oak plus trees. Trees with small branchless part of the stem should be rejected in selecting plus trees by productivity. The share of branchless part of the stem should be at least 40 %.